Optimizing Results of Facial Surgery and Patient Satisfaction with Simultaneous Chemical Peels - Winslow, Catherine (Facial Plastic Surgery, 2019)
Facial antiaging surgery is widely regarded as safe and effective. Current techniques allow us to achieve a balance of restoring youth while minimizing stigmata of surgery to effect a refreshed, natural look. An important component of achieving this goal is to improve the appearance of fine lines and dyschromias which continue to add to the apparent age. Several options exist to improve the appearance of the skin, each with a separate set of indications, advantages, and disadvantages. A medium-depth 35% trichloroacetic acid peel can be safely combined with rejuvenating surgery to enhance patient satisfaction and results with the same downtime and low cost.
Keywords: resurfacing; peel; rejuvenation